Water-soluble polysaccharides of Ganoderma lucidum (W.Curt.:Fr.) P. Karst. (Aphyllophoromycetideae) alleviate the dose-limiting toxicities of irinotecan (CPT-11) - Hu, Z. (2014)
10.1615/IntJMedMushr.v8.i4.30